금강하구언 대량방류시 황해 중동부 해역의 염분분포 - 최현용; 이상호; 유광우; Choi, Hyun-Yong; Lee, Sang-Ho; You, Kwang-Woo (Pada (Hanʼguk Haeyang Hakhoe), 1999)
Hydrographic survey was carried out in the mid-eastern Yellow Sea from Keum River to Taean Peninsula in order to study the motion of the freshwater from the Keum River during July 07-12, 1997 when a large volume of freshwater was discharged from the Keum River weir. The low-salinity (less than 30.0 psu) plume was distributed over the large area between the Keum River and Ochong Island, 60 km northwest off the Keum River mouth. A band of relatively low saline water, originating from the Keum River, was also observed to the north of Ochong Island. The strong haline front had advanced from near Sibidongpa Island to Ochong Island, 25 km northwest of Sibidongpa Island, for 48 hours. A northwestward flow of a speed greater than 0.2 m/s was observed in the surface plume layer to the north of Sibidongpa Island where the water column was strongly stratified. The observed mean flow and the change of the frontal position are interpreted as resulting from the spreading of the Keum River plume. These results suggest that the discharge from the Keum River plays an important role in the coastal circulation of the mid-eastern Yellow Sea adjacent to the river. 금강에서 유출된 담수의 거동 특성을 파악하기 위해, 금강하구에서 담수가 대량 방류된 1997년 7월 7일에서 7월 12일 사이에 한국 서해 중부의 금강하구에서 태안 반도에 이르는 해역에서 해양조사를 실시하였다. 금강하구에서 북서쪽으로 약 60 km 떨어진 어청도 사이의 해역은 30.0 psu 이하의 저염수가 분포하였으며, 어청도 이북해역에서도 부분적으로 금강 담수 기원으로 해석되는 저염수가 관측되었다. 특히 금강 담수 플룸에 의한 것으로 추정되는 염분전선이 십이동파도 인근에서 관측되었으며, 48 시간 후에는 북서쪽으로 약 25 km 떨어진 어청도 근방에서도 관측되어 염분전선의 위치가 시간에 따라 이동하는 결과를 보였다. 담수 플룸에 의해 수직성층이 잘 된 십이동파도 북측해역에서 20 시간 연속 관측된 조류를 분석한 결과 담수 플룸 내인 상층에서 평균유속이 0.2 m/s 이상인 북서방향의 흐름이 관측되었다. 관측된 평균흐름 및 염분전선의 위치변동은 금강 담수 플룸이 외해로 확장되는 과정으로 해석되며, 금강하구에서 유출되는 담수가 금강하구 인근 연안역의 표층해수 순환에 크게 영향을 줄 수 있음을 제시한다.